Effect of Female Education and Sanitation on Infant Mortality in Nepal: Empirical Evidence from District Level Data - Dahal, Madhav Prasad (Economic Journal of Development Issues, 2010)
Child health is a key indicator of the quality of life in all countries. The condition of child health is more vulnerable in least developed countries like Nepal. Definitely there has been a sharp decline in the infant mortality in Nepal since the 1960s.Mother’s education is one of the factors regarded crucial in improving child health. This paper has examined the effect of female education, provision of proper sanitation and absence of access to safe drinking water on infant mortality in Nepal by taking the data that represent 75 districts of Nepal. Key words: Female literacy and average years of schooling; Sanitation and safe drinking water; Infant mortality decline; Nepal Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 44-58